PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN (Studi Kasus Perusahaan LQ45 yang terdaftar di BEI periode 2012-2015) - Sukron Saidy, 13.05.51.0219; Sudarsi, Sri (Students Journal of Economic and Management, 2017)
This research analyzed the influence of Profitability, Liquidity, Leverage, and Size to Dividend Policy of LQ45 Company which is listed on the Indonesia Stock Exchange. A method of the sample using purposive sampling with the same period the end of 2012 until 2015. The data collected were 180 company, but only 29 a company that meet the criteria sample, so that as many as 116 companies that become the sample. Relations and influence between variable explained by using the method regression multiple analysis. The results of the research show that Profitability and the Size of the company have a positive significant effect on Dividend Policy. While Liquidity and Leverage have a negative significant effect on Dividend Policy. Keywords : Dividend Policy, Profitability, Liquidity, Leverage, and Size